Project for Strengthening the Profile of Pancasila Students as a Co-Curricular Program at Elementary School - Nur, Amriani Mustakim; Wardiman, Ade (Cokroaminoto Journal of Primary Education, 2024)
Learning lag, also known as learning lag, occurred due to the relocation of learning spaces during the COVID-19 pandemic. The decline in student abilities causes a decline in the quality of graduates. This condition raises big doubts about the relevance of the previous curriculum (2013 curriculum) to the situation of the Covid-19 pandemic. The aim of this research is to find out how elementary school teachers view P5 as a co-curricular program in implementing a free curriculum. Indicators of co-curricular understanding, P5 objectives, content, process and evaluation will be used to assess teachers' perceptions of P5. Quantitative descriptive research is used to collect data . To collect data, questionnaires were distributed to one hundred elementary school teachers in Enrekang city, and then limited interviews were conducted with three sample teachers to support the questionnaire. For the data, content analysis techniques were used. The results show that teachers' perceptions of P5 are categorized as sufficient based on indicators of co-curricular understanding, objectives, content, processes and evaluation of P5. The interview results showed that the teacher did not understand the flow of P5, the components of the P5 module, and the syntax of P5 activities. As a result, teachers' perceptions of P5 are still categorized as fair or poor. To achieve this, teachers must better understand P5. One way to do this is to use a free learning platform, which is a self-paced teacher training tool that can be accessed anytime and anywhere. It is hoped that the use of free learning platforms will increase teachers' perceptions of P5 as a co-curricular program in the free curriculum.